1990
DOI: 10.1111/j.1365-2621.1990.tb01617.x
|View full text |Cite
|
Sign up to set email alerts
|

Elucidation of the Mechanism of the Acid‐blanch and EDTA Process Inhibition of Clostridium sporogenes PA 3679 Spores

Abstract: Acid-blanching followed by addition of ethylenediamine tetraacetic acid to the can brine had been shown to control germination of mesophilic spores following sub-lethal thermal processes. The mechanism of this control was investigated using C. sporogenes PA 3679 spores in buffered solutions. Spore suspensions in buffered 0.05M citric acid solutions, pH 3.5 and 5.8, and Sorensons phosphate buffer, pH 7.0, were heat-activated at 80 "C and then heated for 5 min at 121 "C. The mechanism of inhibition appeared to i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

1993
1993
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(2 citation statements)
references
References 23 publications
0
2
0
Order By: Relevance
“…This protonization would lead to a collapse of the whole structure, allowing then for the rehydration of the protoplast and for the decrease in heat resistance. To support this view, it has been observed through electron microscopy that the spore cortex reduces in size after heating, and that this reduction is more pronounced when spores are heated in acid medium (Okereke et al 1990). However, if the cortex collapses as a consequence of protonization, spores would be very unstable and, in Warth's opinion (1985), the osmotic pressure created by the cortex is not only caused by the carboxyl groups, but by the whole cortex structure, which includes divalent cations (Stewart et al 1980;Stewart et al 198 1).…”
Section: Sporulation Temperature and Heat Resistance At Different Ph mentioning
confidence: 99%
“…This protonization would lead to a collapse of the whole structure, allowing then for the rehydration of the protoplast and for the decrease in heat resistance. To support this view, it has been observed through electron microscopy that the spore cortex reduces in size after heating, and that this reduction is more pronounced when spores are heated in acid medium (Okereke et al 1990). However, if the cortex collapses as a consequence of protonization, spores would be very unstable and, in Warth's opinion (1985), the osmotic pressure created by the cortex is not only caused by the carboxyl groups, but by the whole cortex structure, which includes divalent cations (Stewart et al 1980;Stewart et al 198 1).…”
Section: Sporulation Temperature and Heat Resistance At Different Ph mentioning
confidence: 99%
“…Okereke et al (17) showed that blanching mushrooms in 0.05 M citric acid and adding EDTA to the brine (acidblanching-chelating process) reduced spoilage of the canned product inoculated with PA 3679 by approximately 30%. Citric acid is traditionally used to lower the pH in brine.…”
mentioning
confidence: 99%